The impact of loneliness and social isolation on the benefits of an exercise program with hospitalised older adults - N. Martínez-Velilla; ML. Sáez de Asteasu; F. Zambom-Ferraresi; A. Galbete; I. Marín-Epelde; MC. Ferrara; J. Yanguas-Lezaún; M. Izquierdo (Elsevier, 2024)
Objectives: This study aimed to assess the prevalence and impact of loneliness (De Jong Gierveld scale) and isolation (Lubben scale) on the effects of a hospital-based exercise programme. Design: Secondary analysis of a randomised clinical trial. Setting: Acute Geriatric Unit of a tertiary hospital in Spain. Participants: 103 hospitalised older adults. Intervention: Individualised multicomponent exercise program (20-minute sessions twice a day for 3 consecutive days). Results: Among the 103 randomised patients included in the analysis (both arms included), 58.3% were male, and their mean age was 87.3 (4.5) years. According to the Lubben scale, 15.8% of patients were at risk of isolation, while 62.7% were in a situation of severe or moderate loneliness according to the De Jong Gierveld scale. In the non-isolated group, training showed a substantial positive impact on Geriatric Depression Scale (B = −1.25, 95% CI = −0.24 to −0.27). In the isolated group, all outcomes improved, but only the Quality of Life showed significant changes (B = 35, 95% CI = 4.96-35.8). The SPPB test (B = 1.62, 95% CI = 0.19-3.04) and Quality of Life, (B = 17.1, 95% CI = 1.84-32.3) showed a significant improvement in the non-loneliness exercise group while no differences were found in the loneliness group. Conclusion: Despite the high prevalence of loneliness and social isolation, individualised exercise programs provide significant benefits to hospitalised patients, especially in quality of life.